2006
DOI: 10.2138/am.2006.1856
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of uranyl minerals: Enthalpies of formation of uranyl oxide hydrates

Abstract: The enthalpies of formation of seven uranyl oxide hydrate phases and one uranate have been determined using high-temperature oxide melt solution calorimetry:[(U02)40(OH)6](H20)5, metaschoepite; P-U02(0H)2; cauo4; Ca(U02)604(OH)6(H20)8, becquerelite; Ca(U02)403(OH)4(H20)2; Na(U02)O(OH), clarkeite; Na2(U0*)604(OH)6(H20)7, the sodium analogue of compreignacite and Pb3(U02)808(OH)6(H20)2, curite. The enthalpy of formation from the binary oxides, AH&, at 298 K was calculated for each compound from the respective dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…Thus, it appears unlikely that hydration contributes more than a small portion of the additional stabilization observed in uranyl carbonates. Similar conclusions appear to hold for uranyl oxide hydrates (Kubatko et al 2006).…”
Section: Resultssupporting
confidence: 76%
“…Thus, it appears unlikely that hydration contributes more than a small portion of the additional stabilization observed in uranyl carbonates. Similar conclusions appear to hold for uranyl oxide hydrates (Kubatko et al 2006).…”
Section: Resultssupporting
confidence: 76%
“…Also, schoepite is a commonly occurring UOH mineral, reported from nearly 80 localities (Plášil 2018 are closely related minerals. A transformation of schoepite to metaschoepite, connected with a loss of the H 2 O molecule from interlayer (i.e., partial dehydration), was observed in air under the room temperature (Christ and Clark 1960;O'Hare et al 1988;Finch et al 1998;Sowder et al 1999;Kubatko et al 2006). From the thermodynamic point of view the process is clearer now, however the exact mechanism remains unknown.…”
Section: Implications For Weathering Of Uo 2+xmentioning
confidence: 99%
“…Recent assessment of the thermodynamics of metaschoepite and β-UO 2 (OH) 2 by Kubatko et al (2006) concluded that metaschoepite (and probably schoepite) may be metastable under all conditions. At 298.15 K, the Gibbs free energy for the reaction UO 3 ·2H 2 O (metaschoepite) = β-UO 2 (OH) 2 + H 2 O(l) is Overall, these calculations based on calorimetric results give little energy difference between metaschoepite, "dehydrated schoepite," and β-UO 2 (OH) 2 , which suggests that kinetic effects probably play a major role in controlling the paths by which "dehydrated schoepite" forms (Fig.…”
Section: Occurrences Of Paulscherreritementioning
confidence: 99%